Acute kidney injury and urinary biomarkers in human immunodeficiency virus–associated cryptococcal meningitis - Schutz, Charlotte; Boulwa, David R.; Huppler-Hullsie, Katherine; Hohenbe, Maximilian von; Rhei, Joshua; Taseera, Kabanda; Thienemann, Friedrich; Muzoora, Conrad; Meya, David B; Meintjes, Graeme (Oxford University Press on behalf of Infectious Diseases Society of America., 2017)
Background. Cryptococcus is the most common etiology of adult meningitis in Africa. Amphotericin B deoxycholate remains paramount to treatment, despite toxicities, including acute kidney injury (AKI). We assessed the ability of the following urine mark- ers to predict AKI in patients who received amphotericin B: urine neutrophil gelatinase-associated lipocalin (NGAL), cystatin C (CysC), tissue inhibitor of metalloproteinases-2 (TIMP-2), and protein. Methods. One hundred and thirty human immunodeficiency virus (HIV)–infected participants with cryptococcal meningitis were enrolled and received amphotericin and fluconazole for 2 weeks. We defined AKI as glomerular filtration rate (GFR) < 60 mL/ min/1.73 m2; measured urine NGAL, CysC, TIMP-2, and protein; and explored AKI incidence, risk factors, and associations with mortality using Cox proportional hazards models. Results. Participants were 48% female with a median age of 35 years, a median CD4 count of 21 cells/μL, and 44% died within 12 months. Incident AKI occurred in 42% and was associated with mortality (adjusted hazard ratio [aHR] = 2.8; P < .001). Development of AKI was associated with female sex (P = .04) and with higher CD4 count (49 vs 14 cells/μL; P < .01). Urine protein level in the highest quartile independently predicted AKI and mortality (aHR = 1.64, P = .04; aHR = 2.13, P = .02, respectively). Urine NGAL levels in the highest quartile independently predicted AKI (aHR = 1.65; P = .04). Conclusions. Acute kidney injury occurred in 42% of patients, and AKI was associated with mortality. Urine biomarkers, specif- ically urine protein, may be useful for antecedent prediction of amphotericin-associated AKI but need further evaluation
Keywords: acute kidney injury; amphotericin B; biological marker; cystatin C; neutrophil gelatinase-associated lipocalin; pro- tein; tissue inhibitor of metalloproteinase